Analytical approaches to study domain formation in biomimetic membranes. Issue 17 (31st July 2017) - Hasan, Imad Younus; Mechler, Adam
Abstract : Novel characterization methods open new horizons in the study of membrane mixtures. Abstract : Domains in biological membranes are linked to a range of biochemical life functions and thus understanding the fundamental physico-chemical drivers of domain formation is one of the key problems of biophysics and chemical biology. The phospholipid bilayer that is the structural basis of the biomembrane is a complex multicomponent mixture, and hence domain formation may be the result of thermodynamic phase equilibria, or specific sequestration of certain lipids; possibly both. There are several obstacles in the way of studying domains and thermodynamic phases in biomembranes: the complexity of the lipid mixture, the two dimensional nature of the membrane and the variety of superstructures the lipid membrane can fold into. Complexity is addressed by the introduction of biomimetic membranes, simplified mixtures of synthetic lipids. Most studies of lipid phase equilibria have been conducted using a biomimetic membrane. This review is intended to address the challenges posed to analytical methodology by the membrane dimensions, while also discussing the question of the reference state. Four key methods are assessed for their strengths and weaknesses in identifying domains and thermodynamic phases in membranes: differential scanning calorimetry, fluorescence microscopy, atomic force microscopy and quartz crystal microbalance. It is demonstrated that, while these methods provide complementary information and thus should be used in tandem, quartz crystal microbalance based nano-viscosimetry measurements offer a breakthrough in measuring phase transition temperatures, and allow the compilation of phase diagrams, of single bilayers of lipid mixtures. By comparing the structural phases of the lipids used for the different methods, it is also shown that the membrane curvature in vesicular lipid samples inhibits the formation of domains which are only observed in flat lamellar membranes, or giant unilamellar liposomes where the role of curvature is negligible.